Nikephoros Gregoras’ “didaskaleion” - ΣΚΛΑΒΕΝΙΤΗ, Αννα Σ. (Byzantina Symmeikta, 2018)
This paper focuses on the foundation and function of a school-“didaskaleion” by Nikephoros Gregoras in the first half of the 14th century (ca. 1325- 1350). Information about this school is provided by Gregoras himself in his Letters, as well as in his History (“Ρωμαϊκὴ Ἱστορία”), whereas secondary data can be traced in his most prominent student’s writings, Isaak Argyros. This institution was located at the Chora Monastery, and, according to Gregoras’ words, its basic aim was to prevent the extinction of learning and to transmit all the knowledge related to “tetraktys”, and especially to astronomy. Besides the inquiry into information about the curriculum and the students of this school, the present study examines thoroughly Gregoras’ pedagogic principles and emphasizes on his rather modern aspect concerning the way he relates child development with education.